2015
DOI: 10.1080/08927022.2015.1032277
|View full text |Cite
|
Sign up to set email alerts
|

GASP: software for geometric simulations of flexibility in polyhedral and molecular framework structures

Abstract: Template-based geometric simulation is a specialised method for modelling flexible framework structures made up of rigid units using a simplified, localised physical model. The strengths of the method are its ability to handle large all-atom structural models rapidly and at minimal computational expense, and to provide insights into the links between local bonding and steric geometry and global flexibility. We review the implementation of geometric simulation in the 'GASP' software, and its application to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…More subtle is the change in the form of the energy landscape; while for β-cristobalite the minimum energy structure lies towards the high volume end of the flexible region, for the borate-analogue it resides towards the low volume end. This is consistent with the findings of Wells et al 40,44 , who have explored the notion of flexibility windows in zeolites and other covalent frameworks and observed that silicates exhibit an atypical tendency to be maximally extended in their relaxed states. This correlates with the absence of any local minimum at small angles in the H3Si-O-SiH3 bending potential ( Figure 8).…”
Section: Cs C2vsupporting
confidence: 92%
“…More subtle is the change in the form of the energy landscape; while for β-cristobalite the minimum energy structure lies towards the high volume end of the flexible region, for the borate-analogue it resides towards the low volume end. This is consistent with the findings of Wells et al 40,44 , who have explored the notion of flexibility windows in zeolites and other covalent frameworks and observed that silicates exhibit an atypical tendency to be maximally extended in their relaxed states. This correlates with the absence of any local minimum at small angles in the H3Si-O-SiH3 bending potential ( Figure 8).…”
Section: Cs C2vsupporting
confidence: 92%
“…The geometric analysis of rotations of the oxygen octahedra performed using the GASP software 32 reveals abrupt broadening of the distributions of rotation angles between x  = 0.47 and x  = 0.53 (Fig. 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Effective polyhedral tilt angles in each final structure were determined using GASP. 55,56 ■ RESULTS AND DISCUSSION Variable-Temperature Diffraction Data and the α oldBi 2 Sn 2 O 7 Model. High-resolution synchrotron X-ray and neutron (Δd/d ≈ 10 −4 Å) powder diffraction data were collected up to 473 K on Bi 2 Sn 2 O 7 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%